Methodological reports: highlights of the study Brazilian Model of Library and Information Studies in the bachelor's level - Amorim da Costa Santos, Placida L. V. [UNESP]; Zins, Chaim (Univ Federal Parana, Dept Ciencia & Gestao Informacao, 2016)
Doctors Placida Santos and Chaim Zins detail the main methodological options of their exhaustive research regarding training professionals in Information Science in Brazil. They emphasize the continuation of studies on the subject and the potential contributions to undergraduate programs in the area.
Keywords: Delphi Study; GroundedTheory; Information profesionals trainning